Plant Population and Row Spacing Affects Growth and Yield of Rainfed Maize in Semi-arid Environments - Haarhoff, Stephanus J.; Swanepoel, Pieter A. (Frontiers in Plant Science, 2022)
Increased tolerance to competition for soil resources of modern maize (Zea mays L.) hybrids increases soil resource use efficiency and yield. Yet little information is available on the relationship between maize population density and yield under no-tillage in semi-arid environments. A 2-year field trial was conducted in South Africa during the 2017/2018 (Season 1) and 2018/2019 (Season 2) production seasons to evaluate growth and water use productivity of rainfed maize established at seven diverse plant population (20 000 to 60 000 plants ha-1) and row spacing (0.52 and 0.76 m) configurations. In Season 1, light interception were 6.8% greater at 0.76 m row spacing compared to 0.52 m row spacing (P < 0.05). In Season 2, despite challenging growing conditions, a well-developed leaf canopy cover was present at 0.52 m row spacing indicating an 10.4% greater IPAR compared to 0.76 m row spacing. In Season 1, with more uniform rainfall distribution, no biomass or yield benefits were found with increased plant population, except at 50 000 plants ha-1 at 0.76 m row spacing. In Season 2, plant populations at 0.76 m row spacing out yielded any given plant population at 0.52 m row spacing. The optimal plant population and row spacing will ultimately be a compromise between obtaining high maize grain yield and minimizing the potential for crop failure in semi-arid environments.